2008
DOI: 10.4055/jkoa.2008.43.6.760
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Radiologic Results of Total Knee Arthroplasty using Electromagnetic Navigation with the Conventional Technique

Abstract: Purpose:We wanted to examine the accuracy of the lower limb alignment and implant positioning that was obtained with using the electromagnetic (EM) navigation technique. Conclusion:The use of EM navigation technique in TKA does not always guarantee the precise alignment of the mechanical axis in all planes, as compared to using the conventional technique. Yet it is useful for obtaining better coronal alignment of the femoral component.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2011
2011

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…Favorable results were documented in the studies carried out by Bellemans et al20) using Robodoc and Mizu-Uchi et al21) using a computed tomographybased navigation system. However, Won et al22) reported that the incidence of outliers was 6% in their study of TKA using an electromagnetic navigation. Bae et al23) suggested the need to be cautious with navigation-assisted TKA in knees with varus deformity based on their observation that the postoperative mechanical axis was more significantly varus in patients with 20°-30° of preoperative varus deformity than those with 10°-20° of preoperative varus deformity.…”
Section: Discussionmentioning
confidence: 97%
“…Favorable results were documented in the studies carried out by Bellemans et al20) using Robodoc and Mizu-Uchi et al21) using a computed tomographybased navigation system. However, Won et al22) reported that the incidence of outliers was 6% in their study of TKA using an electromagnetic navigation. Bae et al23) suggested the need to be cautious with navigation-assisted TKA in knees with varus deformity based on their observation that the postoperative mechanical axis was more significantly varus in patients with 20°-30° of preoperative varus deformity than those with 10°-20° of preoperative varus deformity.…”
Section: Discussionmentioning
confidence: 97%